Experienced fear of crime and its implications for everyday mobilities in later life: an ethnographic case study of an urban Swedish neighbourhood. Issue 2 (3rd July 2017) - Stjernborg, Vanessa
Abstract: This study aims to provide an understanding of the everyday life of older people in a Swedish urban neighbourhood, with a special focus on the experienced fear of crime and how fear may affect mobilities in later life. The paper draws upon in-depth data from an ethnographic case study conducted between December 2011 and April 2013, which followed a group of older people in the neighbourhood of Seved in the city of Malmö, Sweden. The average income in the neighbourhood is one of the lowest in the city, where unemployment is high. Seved is often negatively portrayed in the media, and the residents generally feel more insecure than those in the rest of Malmö. The senior group followed, is part of a municipal project aimed at strengthening networks and enhancing feelings of social participation for older people. Through a variety of activities, the municipality seeks to achieve social sustainability through everyday life mobility and social participation. Findings highlight that news media plays a substantial role in forming perceptions of the neighbourhood. Mental maps and imagined geographies do negatively impact the everyday mobility of persons both inside and outside the area. Some older residents display both avoidance and protective behaviour, which implies that their everyday life mobility is restricted because of their fear of crime. However, social participation and knowing people in the neighbourhood seems to have a salutary effect on their fear of crime and a commendatory effect on their everyday life mobility. The results also raises questions about stereotyping (the Other) and ageism.